2018
DOI: 10.12944/crnfsj.6.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lifestyle Modification Counseling on Glycemic Control in Type 2 Diabetes Mellitus Patients

Abstract: This study was carried out to assess the effectiveness of lifestyle modification counseling using lifestyle intervention holistic model and its adherence towards glycemic control in type 2 diabetes mellitus patients. This quasi-experimental prospective study was conducted among 224 type 2 diabetes mellitus patients in Delhi Diabetes Research Center, New Delhi. The study participants were allocated to lifestyle modification counseling group (intervention) and usual care (control) group based on receiving or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Vários benefícios das intervenções da educação nutricional foram observados paralelamente a melhora da qualidade de vida, no que se refere aos conhecimentos adquiridos, perda de peso, diminuição da circunferência da cintura/quadril, redução da HbA1C e do colesterol total. Outras evidências corroboram os benefícios das intervenções educativas sobre o aumento do conhecimento nutricional (Berrones et al, 2020;Myers et al, 2017), redução do peso e melhorias na composição corporal (circunferência do braço, dobra cutânea do tríceps) (Krishnan et al, 2015), redução da HbA1C (Subhan et al, 2022), sendo que quanto mais intensivas (visita mais frequentes) e/ou mais abrangentes as intervenções, mais são sustentados os resultados na HbA1c (Kumari et al, 2018), em relação aquelas menos intensas ou curtas (Thadchanamoorthy et al, 2021).…”
Section: Discussionunclassified
“…Vários benefícios das intervenções da educação nutricional foram observados paralelamente a melhora da qualidade de vida, no que se refere aos conhecimentos adquiridos, perda de peso, diminuição da circunferência da cintura/quadril, redução da HbA1C e do colesterol total. Outras evidências corroboram os benefícios das intervenções educativas sobre o aumento do conhecimento nutricional (Berrones et al, 2020;Myers et al, 2017), redução do peso e melhorias na composição corporal (circunferência do braço, dobra cutânea do tríceps) (Krishnan et al, 2015), redução da HbA1C (Subhan et al, 2022), sendo que quanto mais intensivas (visita mais frequentes) e/ou mais abrangentes as intervenções, mais são sustentados os resultados na HbA1c (Kumari et al, 2018), em relação aquelas menos intensas ou curtas (Thadchanamoorthy et al, 2021).…”
Section: Discussionunclassified
“…A semi-structured proforma was prepared through an extensive literature review and expert advice to collect the relevant data. [ 6 18 19 ] It was divided into four sections: (A) sociodemographic data, (B) diabetes self-care practices, (C) knowledge of diabetes mellitus, and (D) MA. Score 1 was given to the correct response and zero for other responses.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the included studies are reported in Table 1. Of the 44 studies, 21 were conducted in upper-middle-income countries , 21 in lower-middle-income countries [1,38,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90], and two were conducted in low-income countries [91,92], as grouped by the World Bank criteria [41]. The studies were conducted in diabetes clinics or hospitals (n = 15 [34%]), public or private hospitals/clinics (n = 21[48%]) and community settings/home-based locations (n = 8 [18%]).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Five trials used DM self-management-based coaching programmes [54,67,80,89,91], four trials used the empowerment approach and interactive teaching model [63,64,74,76], and three used the theory of self-efficacy as a theory or model to underpin intervention content [65,66,68]. Each of the following models was used by one trial only: the beliefs, attitudes, subjective norms and enabling factors (BASNEF) model [72]; the predisposing, reinforcing and enabling constructs in educational diagnosis and evaluation (PRECEDE) model [78]; the chronic care model [58]; clinic-based intensified diabetes management model (C-IDM) [60]; the healthbelief model [81]; the comprehensive systematic health education and promotion (SHEP) model [85]; the diabetes comprehensive care model (DCCM) [88]; the structured DSME model [38] and the lifestyle intervention holistic model (LIHM) [90]. The remaining 23 trials Approximately 73% (n = 32) of the interventions were delivered using a face-to-face format, 20% (n = 9) utilising face-to-face intervention with telephone follow-up and 7% (n = 3) using a remotely delivered text message/web-based intervention.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation